Web-Based Posyandu Information System at the Rantau Langkap Village Assistant Health Center: Sistem Informasi Posyandu Berbasis Web di Puskesmas Pembantu Desa Rantau Langkap - Warda Juniarti (International Journal of Technology Vocational Education and Training, 2023)
This study aims to develop a web-based Posyandu information system application at the Sub-District Health Center (Puskesmas) in Rantau Langkap Village as a step towards empowering and providing more effective health services to mothers, infants, and toddlers. Initial observations indicated that the manual data collection process, using methods such as paper-based or peperbase recording, posed challenges for Posyandu workers in monitoring participant data, often resulting in data loss and difficulty reading the handwriting. Therefore, this research introduces a solution by developing a web-based Posyandu information system. The study involves observation and interview methods, with the application of PHP programming language and MySQL as the database. The result is the implementation of a web-based Posyandu information system at the Sub-District Health Center in Rantau Langkap Village, providing ease in the data collection process and the generation of reports on infant and pregnant women data. The system is expected to enhance efficiency, prevent data loss, and ensure readability of information. Thus, this research contributes to efforts aimed at improving community health services at the village level through the utilization of information technology.